PEACE AND SECURITY IN AFRICA: REVISITING ENDOGENOUS RESTORATIVE MECHANISMS? - Omale, Don John O. (EBSU Journal of Social Sciences and Humanities, 2022)
Looking at Africa today, it appears as though the continent has become, in the minds of many around the world, synonymous with all that is wrong with humanity. Genocides, bombings, wars, tribal strife, disease and humanitarian disasters seem to have taken therein, and in the minds of many outsiders, this colouration has reinforced the multifarious stereotypes about Africa as a continent of misery, tribal wars and chaos. To this end, a former British Prime Minister-Tony Blair- in his call on the international community to support the healing of Africa, called ’Africa a scar on the face of the earth’. This paper seeks to promote an academic debate as to whether there are “African solutions to these African problems”. The author interrogates this discourse using ethnography and secondary literature evidence.